STARTUPS DE JORNALISMO: DESAFIOS E POSSIBILIDADES DE INOVAÇÃO // JOURNALISM STARTUPS: CHALLENGES AND OPPORTUNITIES FOR INNOVATION - Bertocchi, Daniela (Contemporanea, 2017)
Muitas vezes confundido com "jornalismo empreendedor" ou "jornalismo freelance", o chamado "jornalismo de startup" transporta em seu próprio nome contornos ainda pouco explorados na literatura científica. A proposta desse artigo é mapear as diferenças, semelhanças e particularidades desses enunciados, buscando refletir sobre como é apresentada a ideia de inovação em cada um deles. Ao final, traz pistas de investigação para posteriores estudos sobre startups jornalísticas e transformações inovadoras no mercado da comunicação. Frequently confused with "entrepreneurial journalism" or "freelance journalism," the so-called "startup journalism" displays in its name some characteristics still not deeply explored in the scientific literature. The purpose of this article is to map the differences, similarities, and particularities of these statements, reflecting on how the idea of innovation is presented in each of them. In the end, it brings in some research clues for further studies on journalism startups and innovative transformations in the communication market.